Business speaking and presentations - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training)
Described how the executive should handle and present their presentation. Explain how to speak in the business environment.
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Business presentations; Business communication